Alterations in the stomatognathic system due to amyotrophic lateral sclerosis (Journal of Applied Oral Science, 2022)
Objectives: To compare the molar bite force, electromyographic activity, chewing efficiency and thickness of the masseter and temporalis muscles in individuals with amyotrophic lateral sclerosis (ALS) and healthy individuals. Material and Methods: Thirty individuals enrolled in the study were divided into the study group (with ALS, n=15) and control group (healthy individuals, n=15). Data regarding molar bite force (right and left), electromyographic activity (mandibular rest, right and left laterality, protrusion, and maximum voluntary contraction), chewing efficiency (habitual and non-habitual), and masticatory muscle thickness (rest and maximum voluntary contraction) were tabulated and subjected to statistical analysis (Student’s t-test, p≤0.05). Results: Comparisons between the groups demonstrated a statistically significant increase in the electromyographic activity of the right masseter (p=0.03) and left masseter (p=0.03) muscles during mandibular rest; left masseter (p=0.00), right temporalis (p=0.00), and left temporalis (p=0.03) muscles during protrusion; and right masseter (p=0.00), left masseter (p=0.00), and left temporalis (p=0.00) muscles during left laterality, in individuals with ALS as compared with healthy individuals. A statistically significant decrease was observed in the habitual chewing efficiency of the right masseter (p=0.00) and right temporalis (p=0.04) muscles in individuals with ALS. No statistically significant difference between the groups was found the masticatory muscle thickness and maximal molar bite force. Conclusions: ALS may lead to modifications in the activities of the stomatognathic system, including muscular hyperactivity and reduction in chewing efficiency; however, no change has been observed in the masticatory muscle thickness and molar bite force.